Capitalisme vert: Les populations locales sur les marchés mondiaux - Magda dos Santos Ribeiro (Confins)
This paper aims to describe and consider the recent agreements signed between Amazonian peoples and transnational and Brazilian corporations. Therefore, the text draws on two distinct sources: a) the ethnographic descriptions, documents and articles published by Brazilian researchers; and b) fieldwork in the community of São Francisco do Iratapuru, located in the state of Amapá, in Brazilian Amazonia, with the local inhabitants (castanheiros) which have for more than 10 years commercial agreements with the largest cosmetics company in Brazil, Natura S/A. The paper argues that such a relationship can not be understood only through the criticism of the advancement of the capitalist model of exchange and exploitation, but must take into account other aspects as important as this: the incorporation of Amazonian alterity and the imaginary of sustainability become fundamental elements in the production of value for the so-called green capitalism.